Impact of the COVID-19 pandemic on the secondary market of real estates. A case study - Słonina, Andżelika; Krzyżek, Robert; De Paola, Pierfrancesco; Maciuk, Kamil (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The topic of the paper is the analysis of the situation in the secondary real estate market in Krakow from 2017 to 2020. The research was conducted based on data obtained from the register of real estate prices and values. The results of the research helped detect changes occurring in the indicated years; the number of transactions in the housing market in the city oscillated around the value of 4,000 for each year. The high demand for real estate was significantly disrupted by 2020 and the outbreak of the COVID-19 pandemic. Despite an almost 50% drop in the number of transactions and reduced interest from potential buyers, the price of 1m2 of residential space rose steadily. Thus, the pandemic only affected the number of transactions, while no deceleration of the rising trend was observed in terms of the average transaction price or the average price per square meter.